Digestibility of Moringa Oleifera Lam. Leaves Meal Based Diet by Oryctolagus Cuniculus. - VIDJANNAGNI, D. Sévérin; TOLEBA, SOUMANOU SEIBOU; Sina, Haziz; DAHOUDA, MOHAMADOU; DAGA, DADJO FLORIAN; Natonnagnon, Ulrich; HAROUNA, Aminath; Aïha, RAT; BABA-MOUSSA, LAMINE SAÏD; Adenile, Adam (My University, 2018)
The use of local feed resources in animal diet can contribute to improve the sustainability of rabbit production. The aim of this work was to evaluate the digestibility of the Moringa oleifera (Lam) leaf meal based diet in rabbits. In this study seven groups of 9 rabbits, aged 40 to 45 days, were fed with 7 different feeds: two commercial feed (ProvA and ProvB), four dried M. oleifera leaf (ML) based diet (Mor10: 10% ML, Mor20: 20% FL, Mor30: 30% FL, and Mor40: 40% ML) and a control diet (CTL). Organic matter digestibility of commercial feed was similar to that of the control feed (P>0.05). The dietary digestibility coefficients Mor10 (62.92%), Mor20 (61.62%) and Mor40 (62.75%) were similar (P>0.05) and lower (P<0.05) than that of Mor30 (69.12%). The highest protein digestibility coefficients were obtained with CTL feed (73.33%), followed by Mor40 (69.83%), Mor10 (69.12%) and Mor30 (68.91%). No difference was observed between the digestive energy utilization coefficients of the feed tested (P>0.05). Weight gains, energy and protein efficiency ratios of feed were similar (P>0.05). The good protein digestibility recorded with the M. oleifera (Lam) leaf feed show that these leaves can be used up to 40% in rabbit feed.
Keywords: Moringa oleifera; Digestibility; Organic matter; Feed efficiency; Oryctolagus cuniculis